The The Use of Kahoot in Assessing Students’ Reading Comprehension - SURYANTI; Masagus Firdaus; Santi Mayasari (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2025)
This study explored the use of Kahoot, a game-based learning platform, in assessing students' reading comprehension of narrative texts among tenth-grade students at SMK Negeri 2 Indralaya Utara. Using a qualitative descriptive method, this research investigated how Kahoot could enhance student engagement and provide meaningful feedback in the reading classroom. Data were collected through classroom observation, student interviews, and document analysis. The findings revealed that Kahoot had a positive effect on students' motivation, encouraged active participation, and helped teachers assess students' understanding in a fun and interactive way. The study suggested that Kahoot could be an effective alternative assessment tool for English language teachers, especially in the context of reading comprehension